Click to Chat

1800-2000-838

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```        prove that:-
sin^6(A) + cos^6(A) = 1 - 3sin^2(A) cos^2(A)```
7 years ago

jagdish singh singh
168 Points
```
```
7 years ago
ANKIT BATHLA
34 Points
```										sin6x+cos6x=(sin2x)3+(cos2x)+3sin2xcos2x(sin2x+cos2x)-3sin2xcos2x(sin2x+cos2x)             =(sin2x+cos2x)3-3sin2xcos2x                           =1-3sin2xcos2x
```
7 years ago
Fawz Naim
37 Points
```										(A+B)^3=A^3+B^3+3AB(A+B)
=>A^3+B^3=(A+B)^3-3AB(A+B)
PUT A=SIN^2(A) AND B=COS^2(A)
SO A^3+B^3  WILL BE  SIN^6(A)+COS^6(A)
NOW SOLVE R.H.S. TO GET THE ANSWER
```
7 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Trigonometry

View all Questions »
• Complete JEE Main/Advanced Course and Test Series
• OFFERED PRICE: Rs. 15,900
• View Details
Get extra Rs. 2,900 off
USE CODE: CHENNA
Get extra Rs. 636 off
USE CODE: CHENNA